Moving Beyond Disciplinary Silos Towards a Transdisciplinary Model of Wellbeing: An Invited Review - Mead, Jessica; Fisher, Zoe; Kemp, Andrew H. (Frontiers in Psychology, 2021)
The construct of wellbeing has been criticised as a neoliberal construction of western individualism that ignores wider systemic issues such as inequality and anthropogenic climate change. Accordingly, there have been increasing calls for a broader conceptualisation of wellbeing. Here we impose an interpretative framework on previously published literature and theory, and present a theoretical framework that brings into focus the multifaceted determinants of wellbeing and their interactions across multiple domains and levels of scale. We define wellbeing as positive psychological experience, promoted by connections to self, community and environment, supported by healthy vagal function, all of which are impacted by socio-contextual factors that lie beyond the control of the individual. By emphasising the factors within and beyond the control of the individual and highlighting how vagal function both affects and are impacted by key domains, the biopsychosocial underpinnings of wellbeing are explicitly linked to a broader context that is consistent with, yet complementary to, multi-levelled ecological systems theory. Reflecting on the reciprocal relationships between multiple domains, levels of scale and related social contextual factors known to impact on wellbeing, our GENIAL framework may provide a foundation for a transdisciplinary science of wellbeing that has the potential to promote the wellbeing of individuals while also playing a key role in tackling major societal challenges.